Experimental investigation and optimization of nano Al2O3 mixed FSWed joint between AA2024-T351 and AA7075-T651 by response surface approach - Gebreamlak, Getachew; Palani, Sivaprakasam; Sirahbizu, Belete; Čep, Robert (Frontiers in Mechanical Engineering, 2024)
Additive mixed friction stir welding can be an innovative and novel method for enhancing the friction stir welding process. Thus, this research aimed to investigate nano Al2O3 effects on the mechanical and microstructure of FSWed joints using Al alloys AA2024-T351/AA7075-T651. The experiments were performed based on response surface approach based CCD twenty run with varying three factors: tool rotational speed (A: 800-1200 rpm), welding speed (B: 20-60 mm/min), tool plunge depth (C: 0.2-0.4 mm) and fixed volume percentages of Al2O3 nano-particles (8%). Mechanical performances such as tensile, yield, and hardness tests have been performed and microstructural properties have been analyzed through SEM and microscopy. The statistical analysis shows that the tensile strength can be significantly affected by rotational speed (A), welding speed (B), tool plunge depth (c), interaction (AB, BC, AC), and quadratic term A2, B2 in the FSW process; yield strength was influenced considerably by main, interaction, and quadratic terms; main factors and quadratic terms A2, B2 and C2 significantly influenced hardness values. The fracture test revealed that the joints with Al2O3-reinforced AA2024-T351/AA7075-T651 alloys were more ductile and less brittle. The optimal conditions for FSW, tool rotational at 1146 rpm, weld speed at 60 mm/min, and 0.4 mm plunge depth were responsible for higher tensile strength of 169 MPa, yield strength of 145 MPa, and micro-hardness values of 89 HRB due to the uniform nano-particle dispersions and better material mixing.